KEKERINGAN CUACA DAN KEBAKARAN HUTAN DI TAMAN NASIONAL BERBAK, SUMATERAWEATHER DROUGHT INDEX AND FIRE IN BERBAK NATIONAL PARK, SUMATERA - A. Asril; Daniel Murdiyarso; Bambang Hero Saharjo (Agromet, 2003)
Abstract is available in the full text (pdf format)